PENGARUH LATIHAN KARET TERHADAP PUKULAN GYAKU TSUKI PADA ATLET KARATE KUMITE BUKIT BARUGA ANTANG - Andi Syahrul Ginayah; Wahyudin Wahyudin; Etno Setyagraha (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2022)
While the purpose of this study was to determine the effect of rubber training on gyaku tsuki strokes in Karate Kumite athletes in Bukit Baruga Antang. In this research design, research subjects were selected by purposive sampling based on certain characteristics to become a research group so that the research subjects were homogeneous. The research subjects in this study were soccer athletes from Persinbar. consisting of 15 male athletes. While data analysis using SPSS 21 using descriptive test, normality test and hypothesis testing.Based on the results of the analysis, it can be seen that the results of data processing can be seen that the T-Test obtained is the value of the influence of rubber training on gyaku tsuki punches in Bukit Baruga Antang kumite athletes, the initial test of the effect of rubber training on gyaku tsuki punches on Bukit Baruga Antang kumite athletes obtained from The data on the initial test value of the gyaku tsuki stroke on the Kumite Dojo karate athlete in Bukit Baruga Antang obtained an average value of 15.4667 and obtained a P value of 0.000 (P <0.05), and the data above is the final test of the effect of rubber training on gyaku tsuki strokes in karate athletes. Kumite dojo Bukit Baruga Antang obtained an average value of 16.3333 and obtained a P value of 0.000 (P <0.05). From the data above, it can be seen that there was also an increase in the effect of rubber training on gyaku tsuki strokes in Kumite Dojo athletes at Bukit Baruga Antang with a difference of -86667